2021
DOI: 10.1093/mnras/stab3127
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons in Seyfert and star-forming galaxies

Abstract: Polycyclic Aromatic Hydrocarbons (PAHs) are carbon-based molecules resulting from the union of aromatic rings and related species, which are likely responsible for strong infrared emission features. In this work, using a sample of 50 Seyfert galaxies (DL < 100 Mpc) we compare the circumnuclear (inner kpc) PAH emission of AGN to that of a control sample of star-forming galaxies (22 luminous infrared galaxies and 30 H ii galaxies), and investigate the differences between central and extended PAH emission.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 115 publications
3
26
0
Order By: Relevance
“…This is in agreement with the literature since the 6 µm feature is likely excited by SF-related emission, while the feature at the longer wavelength could be more affected by the presence of AGN, whose dust-reprocessed emission peaks in the 10-30 µm regime (e.g., Mullaney et al 2011). The depleted PAH luminosity in the presence of nuclear activity is consistent with the recent results from García-Bernete et al (2022), who observed depleted PAH emission in the nuclear region of local AGN and found that AGNdominated objects show PAH luminosities similar to those of SFGs at larger distances from the nucleus. Thus, the extrapolation of the molecular gas mass from the PAH feature luminosity (e.g., as suggested by Co19) can induce a significant underestimation of M H 2 if the presence of nuclear activity has not been properly identified, as happens in the case of heavy extinction of weak nuclear emission; this is the case of some local, extremely obscured Seyfert 2 galaxies (e.g., Marchesi et al 2018).…”
Section: Pah As Tracer Of the Molecular Gassupporting
confidence: 92%
“…This is in agreement with the literature since the 6 µm feature is likely excited by SF-related emission, while the feature at the longer wavelength could be more affected by the presence of AGN, whose dust-reprocessed emission peaks in the 10-30 µm regime (e.g., Mullaney et al 2011). The depleted PAH luminosity in the presence of nuclear activity is consistent with the recent results from García-Bernete et al (2022), who observed depleted PAH emission in the nuclear region of local AGN and found that AGNdominated objects show PAH luminosities similar to those of SFGs at larger distances from the nucleus. Thus, the extrapolation of the molecular gas mass from the PAH feature luminosity (e.g., as suggested by Co19) can induce a significant underestimation of M H 2 if the presence of nuclear activity has not been properly identified, as happens in the case of heavy extinction of weak nuclear emission; this is the case of some local, extremely obscured Seyfert 2 galaxies (e.g., Marchesi et al 2018).…”
Section: Pah As Tracer Of the Molecular Gassupporting
confidence: 92%
“…2. This is broadly in agreement with IRS results for AGN-dominated sources (Diamond-Stanic & Rieke 2010;García-Bernete et al 2022).…”
Section: Nuclear Versus Sf Pah Propertiessupporting
confidence: 92%
“…from García-Bernete et al 2022). The values of the 6.2/7.7 µm PAH ratios for the nuclear region of NGC 6552 are located in the region of large PAH molecules (N c ∼ 400; see the top panel of Fig.…”
Section: Nuclear Versus Sf Pah Propertiesmentioning
confidence: 94%
See 1 more Smart Citation
“…The mid-IR regime also provides strong evidence that an AGN affects its host galaxy's dust. As already brought up in Section 5.1, an AGN appears to affect both the size and ionization fraction of the PAH [69,163,164]. There may also be PAH carrier destruction as well but this appears to be localized to the nuclear regions around the AGN rather than the extended galaxies and affects shorter wavelength PAH features more than longer wavelength ones such as 11.3 µm (e.g., [50,66]).…”
Section: Dust Properties Around Agnmentioning
confidence: 86%